State Regulation of Environmental Taxes and Fees: National and International Experience - GRUNDEL, Larisa Petrovna; NAZAROVA, Natalia Alexandrovna; KOSTIN, Alexey Alexandrovich; KNIAZEVA, Anastasia Viktorovna; GORBATKO, Elena Samratovna (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.11.1(41).18, 2020)
The purpose of this paper is to substantiate the directions of improvement in state regulation of environmental taxes and fees (ecotax regulation) as an instrument of public environmental policies. The dialectical, historical and structural methods are used to detect the preconditions and specifics of ecotax regulation in addressing environmental issues. The method of expert survey is also employed to analyse whether the international practice of ecotax regulation can be implemented in Russia. The paper explores the fundamentals of environmental taxation as a meaningful component of the overall economic policy measures; environmental taxes and charges adopted in the world are analysed. In the expert survey, a specific focus is ecotax regulation issues with respect to environmentally harmful products.